2014
DOI: 10.1016/j.bmc.2014.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and optimization of a new class of pyruvate kinase inhibitors as potential therapeutics for the treatment of methicillin-resistant Staphylococcus aureus infections

Abstract: A novel series of bis-indoles derived from naturally occurring marine alkaloid 4 were synthesized and evaluated as inhibitors of methicillin-resistant Staphylococcus aureus (MRSA) pyruvate kinase (PK). PK is not only critical for bacterial survival which would make it a target for development of novel antibiotics, but it is reported to be one of the most highly connected ‘hub proteins’ in MRSA, and thus should be very sensitive to mutations and making it difficult for the bacteria to develop resistance. From t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 13 publications
2
35
0
Order By: Relevance
“…These findings also support the proposition put forth by Zúñiga-Ripa et al (27) that Brucella strains rely on the simultaneous catabolism of carbohydrates (e.g., glucose) and amino acids (e.g., gluconeogenic substrates) to support their intracellular replication in mammalian hosts. From a practical perspective, the independent roles that PykM and PpdK play in the virulence of B. abortus 2308 make them both attractive targets for the development of chemotherapeutic agents, and in fact, preliminary studies have shown that some of the bis-indole class of synthetic pyruvate kinase inhibitors (37) To the authors' knowledge, the Bradyrhizobium and Brucella PykM proteins are the only members of this class of pyruvate kinases that have been examined. However, the observation that neither of these enzymes is allosterically regulated by fructose-1,6bisphosphate (FBP) or AMP is notable.…”
Section: Discussionmentioning
confidence: 99%
“…These findings also support the proposition put forth by Zúñiga-Ripa et al (27) that Brucella strains rely on the simultaneous catabolism of carbohydrates (e.g., glucose) and amino acids (e.g., gluconeogenic substrates) to support their intracellular replication in mammalian hosts. From a practical perspective, the independent roles that PykM and PpdK play in the virulence of B. abortus 2308 make them both attractive targets for the development of chemotherapeutic agents, and in fact, preliminary studies have shown that some of the bis-indole class of synthetic pyruvate kinase inhibitors (37) To the authors' knowledge, the Bradyrhizobium and Brucella PykM proteins are the only members of this class of pyruvate kinases that have been examined. However, the observation that neither of these enzymes is allosterically regulated by fructose-1,6bisphosphate (FBP) or AMP is notable.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to improve alkaloid activity through synthetic modifications have been successful when using indole, isoquinoline, pyrrole, and thiazole alkaloids as scaffolds. In the indole class, a β-carboline dimer (NCD9; Supplementary Table 1) and simple indole dimer (5,6,6'-tribromo-1H,1'H-2,2'-biindole) have been synthesised with respective MICs of 0.1-4.0 µg/mL [83] and 0.5 µg/mL [84] against Grampositive pathogens. Also, a manzamine A derivative has been produced (8-n-hexamidomanzamine A)…”
Section: Semisynthetic and Synthetic Alkaloidsmentioning
confidence: 99%
“…We shed new light on known syntheses of -bromo-1-(1H-indol-3-yl)-ethanones (15)(16)(17)(18) and indolyl-3-carbonylnitriles (27)(28)(29)(30) and in the process have gained new mechanistic insight into these useful transformations. Finally, we have confirmed the pivotal contribution of the piperazine-2-one and imidazole rings to the MRSA PK inhibition of cis-3,4-dihydrohamacanthin B and bromodeoxytopsentin respectively.…”
Section: Resultsmentioning
confidence: 98%
“…11 Recently a series of novel halogenated bisindoles were found to potently inhibit MRSA PK highlighting the importance of the bisindole scaffold to the pharmacophore. 15 X-ray analysis of 1 bound to MRSA PK indicated that this compound was located in a symmetrical hydrophobic binding pocket located at the small interface of the MRSA PK homotetramer, wedged between two prominent aromatic histidine (HIS365) residues (Figure 1). 11 From the potent inhibition (16 and 60 nM) of MRSA PK observed for both the piperazine-2-none and imidazole containing bisindoles 1 and 2 respectively, 11 we decided to extend the structure activity relationship study of these bisindole alkaloids, through bioisoteric replacement of the imidazole ring of 2 with a thiazole ring, in which a hydrogen bond accepting sulfur atom replaced the hydrogen bond donor (NH) present in both the imidazole and piperazine rings.…”
Section: Introductionmentioning
confidence: 98%